DAMPAK DESA WISATA TERHADAP PENGEMBANGAN EKONOMI LOKAL KELUARGA MISKIN DI DESA TEPUS, KAPANEWON TEPUS KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Ramadhany, Nour Malita Azahra; Suradi, Suradi; Nainggolan, Atirista (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2025)
This research aims to determine the impact of the existence of the Tepus Tourism Village on the local economic development of poor families in Tepus Village based on three aspects including 1) Aspects of changes in income levels, 2) Aspects of employment opportunities, and 3) Aspects of partnerships. This research uses a quantitative approach with descriptive methods. Sampling in this study used a simple random sampling technique with a sample size of 82 respondents. Data collection techniques are carried out through: 1) Questionnaires, 2) Unstructured interviews, and 3) Documentation studies. The results of this research show that the tourist village in Tepus Village has a significant positive impact on local economic development for poor families. This positive impact can be seen from a significant increase in three aspects, namely changes in income levels, employment opportunities and partnerships which jumped from the low to high category after the village was designated as a tourist village. tour. However, in every aspect, several problems are still found, such as the low income of poor families, limited skills possessed by poor families, and the inadequate capabilities of the Tourism Awareness Group (Pokdarwis) as tourism village managers. Some of these problems are related to each other, which means that the impact of the tourist village is still not evenly felt by poor families in Tepus Village. For this reason, a program is recommended in the form of the "Sejahtera Mandiri Village Program" to make the Tepus Tourism Village into an independent, prosperous and competitive village which will be achieved through empowerment and increasing welfare for poor families, local economic development, and fair tourism village development. and sustainable.